Investigating the Effect of Probiotics as Natural Preservatives on the Microbial and Physicochemical Properties of Yogurt-Marinated Chicken Fillets - Behzad Masoumi; Azam Abbasi; Seyed Mohammad Mazloomi; Samaneh Shaghaghian (Journal of Food Quality)
Microbial flora of probiotic yogurt can have nutraceutical properties and improve beneficial health effects of food products. In this study, microbial and physicochemical properties of raw chicken fillets dipped in regular yogurt and probiotic yogurt containing Lactobacillus casei, preserved at 4°C for 9 days, were studied. In this regard, microbial analysis (Staphylococcus aureus, fecal coliform, yeasts, and molds) and physicochemical analysis (pH, water holding capacity, cooking loss percentage, Thiobarbituric acid reactive substances, and texture profile analysis) were performed during the storage time. In comparison with control samples, the amount of Staphylococcus aureus, fecal coliforms, yeast and mold counts, pH index, malondialdehyde value, and cooking loss percentage reduced significantly (P<0.05) in the chicken fillets treated with regular and probiotic yogurt, while the water holding capacity increased in six days. It was concluded that probiotic and regular yogurts reduced microbial growth and improved the physicochemical quality of chicken fillets during storage and cooking time.